Reply to the Letter to the Editor concerning “Posterior deltoid shoulder tightness and greater contralateral lower limb muscle strength are associated with swimmers' shoulder pain” - Matsuura, Yuiko (Journal of science and medicine in sport, 2024)
[...]as pointed out by the authors, the current study indeed lacks assessment measures related to exercise performance. [...]the prioritization of muscle stiffness indices using shear wave elastography was paramount, while the selected measures, such as internal and external rotation range of motion and muscle strength of the shoulder joint, which are believed to be related to muscle stiffness, were based on this objective. [...]since none of the subjects in this study were smokers and none of the swimmers consumed alcohol daily, it is unlikely that unhealthy lifestyle habits such as smoking and excessive drinking contributed to swimmer's shoulder pain in our cohort study. [...]given that a relationship between sleep duration and injury occurrence in athletes has been reported,5,6 it is important to consider the lifestyle habits noted by the authors and further examine them in athlete populations.